2012
DOI: 10.5367/oa.2012.0103
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Efficiency of India's Horticultural Commodities under Different Supply Chains

Abstract: India's horticulture sector is growing and playing a vital role in the continent's agricultural economy. India is the second largest producer of fruit and vegetables globally, but horticultural development is currently constrained by poor marketing. The gap between prices received by farmers and those paid by consumers is large, reflecting inefficient marketing arrangements. This study estimates the market costs, market margins, price spread, the producer's share of the consumer's rupee and the market efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
1
10
0
Order By: Relevance
“…The finding is also consistent with Dastagiri (2010) who concluded the highest percentage of benefit goes to potato wholesalers. The study result further indicated that the intermediaries play a crucial role in securing their profit margins.…”
Section: Profit Margin and Share Of Profit Along Potato Marketing Channelssupporting
confidence: 90%
“…The finding is also consistent with Dastagiri (2010) who concluded the highest percentage of benefit goes to potato wholesalers. The study result further indicated that the intermediaries play a crucial role in securing their profit margins.…”
Section: Profit Margin and Share Of Profit Along Potato Marketing Channelssupporting
confidence: 90%
“…The concept of efficiency is simply measured by the output-input ratio (Sartina et al, 2021;Dastagiri et al, 2012). Similarly, efficient marketing is the ultimate goal to be achieved in the marketing system (Alderson, 2006;Gruen, 1997).…”
Section: Marketing Efficiencymentioning
confidence: 99%
“…Accordingly, the study extends the existing literature by linking the matters of the efficiency of marketing and distribution channels and input costs, which could possibly affect the selling price at the corn producer level. These two matters together could cause a severe impact on producer's welfare (Dastagiri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the traditional Indian AFSC was empirically analyzed by the set of survey articles (Dastagiri et al, 2012;Hegde and Madhuri, 2013;Mitra et al, 2018;Negi and Anand, 2019;Panda and Sreekumar, 2012;Raghunath and Ashok, 2009) and reported the costs incurred in the distribution of products from farmers to customers. These authors reported that the small farmers individually transport their products from village to market in which they have to bear higher transportation cost in the range of 30-40% of total transactions costs.…”
Section: Literature Reviewmentioning
confidence: 99%